2003
DOI: 10.1182/blood-2002-06-1725
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant PfEMP1 peptide inhibits and reverses cytoadherence of clinical Plasmodium falciparum isolates in vivo

Abstract: The parasite ligand Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) and host endothelial receptors represent potential targets for antiadhesive therapy for cytoadherence. In the present study, the major host receptor CD36 was targeted in vitro and in vivo with a recombinant peptide, PpMC-179, corresponding to the minimal CD36-binding domain from the cysteine-rich interdomain region 1 (CIDR1) within the MCvar1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
(34 reference statements)
1
24
0
Order By: Relevance
“…5A). Fifty percent inhibition of binding to CD36 was seen at a concentration of 5 to 6 M of CIDR-f, a result in line with previous studies (10,40). We also tested inhibition of PE adherence of P. falciparum strains 3D7, HB3, and FCR3, selected for either CD36 or CSA binding, using truncated and chimeric proteins at a concentration of 6 M. At this concentration CIDR-f as well as 1640-f showed 40 to 60% inhibition of PE adherence to HLEC-CD36 in all three strains, while all the other recombinant proteins tested showed negligible inhibition (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…5A). Fifty percent inhibition of binding to CD36 was seen at a concentration of 5 to 6 M of CIDR-f, a result in line with previous studies (10,40). We also tested inhibition of PE adherence of P. falciparum strains 3D7, HB3, and FCR3, selected for either CD36 or CSA binding, using truncated and chimeric proteins at a concentration of 6 M. At this concentration CIDR-f as well as 1640-f showed 40 to 60% inhibition of PE adherence to HLEC-CD36 in all three strains, while all the other recombinant proteins tested showed negligible inhibition (Fig.…”
Section: Resultssupporting
confidence: 80%
“…This is reminiscent of immunoglobulin molecules, where a limited number of loops variable in length and in sequence determining the binding specificity of the molecule are presented on an essentially conserved structural framework (21,26). Work using the MCr179 recombinant protein demonstrated that the binding of PEs from a variety of parasite lines to CD36 can be specifically inhibited by competition with the recombinant protein and that the addition of the protein to an in vivo mouse model led to the desequestration of PEs (40). This contrasted with the inhibitory effect of antibodies raised against the same protein, where adherence of PEs was inhibited only in a strain-specific fashion, with limited effects seen on CD36 binding of PEs other than the MC strain (4).…”
Section: Discussionmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) was performed with the pPMC-y179 recombinant protein (47). One hundred microliters of a 1-g/ml solution of the recombinant protein in PBS was added to Immunolon 4 HBX plates and incubated overnight at 5°C.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant protein Sc y179 was expressed in Saccharomyces cerevisiae VK1 cells and was purified from the supernatant by nickel-nitrilotriacetic acid-agarose chromatography as described previously (3). Recombinant protein Pp MC-179 was expressed in Pichia pastoris and was purified by using nickel-nitrilotriacetic acid followed by size exclusion chromatography and reverse-phase high-performance liquid chromatography (47). Bacterial glutathione S-transferase (GST) and GST-r179 (MC rC1-2 [1-179]) were prepared as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…PfEMP-1 domains might be regarded as ideal candidates for subunit vaccine development, since most complications that characterize severe malaria are likely to be prevented by antibodies that inhibit the PfEMP-1-mediated binding of infected RBCs to specific endothelial receptors. Although the extensive diversity in PfEMP-1 represents a major obstacle for immunization, its motifs that bind to CD36 and CSA are structurally conserved (44,96), pointing to these domains as attractive targets for vaccines aimed at the inhibition or reversal of cytoadherence (65,120).…”
Section: Antigenic Variationmentioning
confidence: 99%